Factors impacting adoption of electronic HRM in public sector organizations: Case study of Hudury mobile attendance application in Ministry of Education in the Saudi Arabia - Alduraywish, Yousef (Politeknik Elektronika Negeri Surabaya (PENS), 2025)
This study investigates the factors influencing the adoption of the Hudury electronic attendance system among employees of the Ministry of Education (MOE) in Saudi Arabia. Using the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), this research examines the impact of perceived ease of use (PEOU), perceived usefulness (PU), trust, security, attitude, and behavioral intentions on actual system usage. A non-probability sampling technique was employed to collect 225 responses from employees across three MOE departments through an online survey. Statistical analysis revealed that PEOU, PU, security, and attitude significantly and positively influence the adoption of Hudury. However, while trust and behavioral intention also have a positive impact, their effects on system adoption were found to be statistically insignificant. These findings highlight the importance of addressing trust deficits by conducting training sessions on Hudury’s efficacy to enhance employees' behavioral intentions toward its use. The study is limited by its non-probability sampling method, which may affect the generalizability of the findings to the broader MOE workforce.